Two sides of the same coin? Biodiversity conservation and extractivism in Latin America - Klier, Gabriela (2017)
In this work we focus on the analysis and comparison of the assumptions underlying two types of human practices that are identified as antagonistic: the current model called "extractivist" and the hegemonic practices related to conservation, particularly from Conservation Biology. We analyzed three common assumptions common to these practices: their global character, the exclusion of human living and the reification of nature. Our hypothesis states that extractivism and biodiversity conservation present complementary pillars, referring to the relationship between human and environment as well as the conception of Nature. In turn, we seek to recover certain proposals within conservation that dispute the hegemonic perspective in order to draw new horizons in environmental care.